Considerations on the role of federalism in managing ethnic plurality in multinational states in conflict prevention - Rodrigues, Daniel (2014)
The existence of several ethnic, religious and/or linguistic groups whose rights are not acknowledged or are continuously violated leads to tension with unpredictable consequences. If, in some cases, those groups use peaceful means to ensure that their specificities are acknowledged but, in other cases, there is frequent use of force to attain the same goals. This type of conflict occurred in the western Balkans in the 1990s or still take place in regions such as the Caucasus, the Democratic Republic of Congo, Nigeria or Myanmar in which the ethnic element, together with the religious issue, are the main causes. Though it is true that several solutions have been presented to respond to the tensions inherent to ethnic diversity of multinational States, it is also true that the several theoretical practical models have not always met the objectives and, above all, resolved situations of peace, which are often of negative peace. From minority rights to federalism, we may identify principles whose importance and adequacy to contexts may be defined as formal peace. Nevertheless, it remains important to include and frame those elements within specific cases, considering that each case is different and adapting these principles to a specific situation does not prevent them from being inadequate to a situation apparently similar. It is therefore crucial that considerations are raised on the role a political and administrative organization model such as federalism may play, partly as a complement to the law of minorities as a tool to manage ethnic diversity in States that may be defined as multinational, as well as to prevent ethnic conflicts.